2011
DOI: 10.1007/s13277-011-0214-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the phenotype pattern of macrophages isolated from malignant and non-malignant pleural effusions

Abstract: Macrophages are among the infiltrate components of most malignant tumors. Tumor-associated macrophages (TAMs) may secrete a variety of humoral factors, which promote or inhibit tumor growth. In general, depending on their activation pathway, macrophages exhibit two different patterns of phenotype, M1 or M2. It is assumed that TAMs comprise pattern M2. In the malignant pleural effusion, macrophages are a frequent component of cytological evaluation. In this microenvironment, TAMs could be involved in the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…Previous studies have revealed that M2 macrophages represent a major component in malignant pleural effusion (MPE). These M2 macrophages have been suggested to functionally support the growth of tumors by inhibiting anti-tumor T cell immunity [40]. In this study, we found that M .…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have revealed that M2 macrophages represent a major component in malignant pleural effusion (MPE). These M2 macrophages have been suggested to functionally support the growth of tumors by inhibiting anti-tumor T cell immunity [40]. In this study, we found that M .…”
Section: Discussionsupporting
confidence: 51%
“…In addition to established clinical variables, 12 potential immune response-related genes were found to be significantly associated with poor survival. These included genes known to be expressed by microglia (CCL8 [35], SPP1 [36], IRF7 [37], IL1RAP [38]), macrophages (IL1RN [39], SPP1 [40], PDPN [41], IL1RAP [42], MDK [43], TFRC [44], HRH4 [45]), and tumor-associated macrophages (IL6 [46], SPP1 [47]). Many of the corresponding gene products are also known to influence monocyte/microglia/macrophage recruitment and activation (IL6 [48], SPP1 [49], CCL8 [50], MDK [51]).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages isolated from malignant and reactive effusions were shown to have a different antigenic profile, with CCR7 expression being significantly higher in nonmalignant effusions [36]. …”
Section: Fc In Effusion Researchmentioning
confidence: 99%